2017
DOI: 10.1016/j.ahj.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus is a coronary heart disease risk equivalent for peripheral vascular disease

Abstract: Background Diabetes Mellitus (diabetes) is associated with significantly increased risk of peripheral vascular disease (PVD). Diabetes is classified as a coronary heart disease (CHD) risk equivalent, but it is unknown whether diabetes is a CHD risk equivalent for PVD. Objectives To evaluate the odds of peripheral arterial disease (PAD) or carotid artery stenosis (CAS) among participants with diabetes, CHD or both, compared to participants without diabetes or CHD, in a nationwide vascular screening database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 26 publications
1
24
0
1
Order By: Relevance
“…The dataset contained screening results collected between 2003 and 2008 from 3,696,778 mostly self-referred adults in all 50 US states. Before undergoing the screening procedure, individuals completed a questionnaire that included information on demographics, smoking, exercise, cardiovascular risk factors, medical comorbidities, and family history of atherosclerosis and vascular disease [11,12]. For the purposes of this study, peripheral vascular disease is defined as lower extremity periphery artery disease (PAD) or carotid artery stenosis (CAS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dataset contained screening results collected between 2003 and 2008 from 3,696,778 mostly self-referred adults in all 50 US states. Before undergoing the screening procedure, individuals completed a questionnaire that included information on demographics, smoking, exercise, cardiovascular risk factors, medical comorbidities, and family history of atherosclerosis and vascular disease [11,12]. For the purposes of this study, peripheral vascular disease is defined as lower extremity periphery artery disease (PAD) or carotid artery stenosis (CAS).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent analyses demonstrated that it was only in the presence of multiple cardiovascular disease risk factors that diabetes conferred risk of CHD similar to the risk experienced by those with prior CHD events [10]. Recent analysis demonstrated that diabetes is also a CHD-risk equivalent for the outcome of peripheral vascular disease [11]. However, whether the relationship between diabetes and peripheral vascular disease varies by presence of cardiovascular disease risk factors has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Current smoking was associated with the highest odds of PAD. These researchers had previously demonstrated that CAD and diabetes synergistically increase the odds of PAD [6]: indeed, individuals with both diabetes and CAD have odds of developing PAD greater than the product of their individual odd ratios.…”
Section: Are Diabetic Patients Without Heart Disease At Higher Rismentioning
confidence: 99%
“…Diabetes mellitus (DM) is considered to have a risk equivalent to that of coronary heart disease, and global prevalence is gradually increasing [8,9]. Diabetic cardiovascular autonomic neuropathy contributes to inappropriate perception of chest pain [10].…”
Section: Introductionmentioning
confidence: 99%